Action Seniors! Cost‐Effectiveness Analysis of a Secondary Falls Prevention Strategy Among Community‐Dwelling Older Fallers. Issue 9 (29th May 2020) - Davis, Jennifer C.; Khan, Karim M.; Hsu, Chun Liang; Chan, Patrick; Cook, Wendy L.; Dian, Larry; Liu‐Ambrose, Teresa
Abstract : BACKGROUND: The Otago Exercise Program (OEP) has demonstrated cost‐effectiveness for the primary prevention of falls in a general community setting. The cost‐effectiveness of exercise as a secondary falls prevention (ie, preventing falls among those who have already fallen) strategy remains unknown. The primary objective was to estimate the cost‐effectiveness (incremental cost‐effectiveness/utility ratio) of the OEP from a healthcare system perspective. DESIGN: A concurrent 12‐month prospective economic evaluation conducted alongside the Action Seniors! randomized critical trial (OEP compared with usual care). SETTING: Vancouver Falls Prevention Clinic (Vancouver, BC, Canada; http://www.fallsclinic.ca ). PARTICIPANTS: A total of 344 community‐dwelling older adults, aged 70 years and older, who attended a geriatrician‐led Falls Prevention Clinic in Vancouver, after sustaining a fall in the previous 12 months. MEASUREMENTS: Main outcome measures included: incidence rate ratio for falls, healthcare costs, incremental cost per fall prevented, and incremental cost per quality‐adjusted life year (QALY) gained. RESULTS: The OEP costs $393 CAD per participant to implement. The incremental cost per fall prevented resulted in a savings of $2 CAD. The incremental cost per QALY gained (where QALYs were estimated using the Euro‐Qol 5D three‐level version [EQ‐5D‐3L]) indicated the OEP was less effective than usual care. The incremental cost per QALY gained (where QALYs were estimated using the Short Form 6D [SF‐6D]) indicated the OEP was more effective and less costly than usual care. The incremental QALYs estimated using the EQ‐5D‐3L and the SF‐6D were not clinically significant and close to zero, indicating no change in quality of life. CONCLUSION: Compared with usual care, healthcare system costs are saved and falls are prevented when older fallers who attend a geriatrician‐led falls clinic are allocated to, and provided, the physiotherapist‐guided exercise‐based falls prevention program (the OEP).